Studying the Effect of the Trailing Edge Blowing of NACA0018 Airfoil on the Aerodynamic Performance - Alsahlani, Ahmad A.; Al-Saad, Mohammed; Radhi, Zainab K. (Basrah Journal for Engineering Sciences, 2024)
The flow control around the airfoil is widely investigated and utilized in the aircraft industry. The benefit of reducing the separation effect and its impact on the aerodynamic performance made the effort on this area is more desirable as this will impact to enhance the flight control as well as to reduce the fuel consumption during the flight. In this paper, the flow control using leading-edge blowing technique has been conducted for NACA0018 airfoil at Reynolds number 6.85 and 13.7 × 10 5 . A CFD analysis has been conducted to examine several flight parameters and blowing speed to explore the benefit of using the blowing in this wing section. The results indicate that the lift coefficient can be enhanced to be increased by 4-6% as compared with no blowing case. However, this increase ratio is affected by the operational Reynolds number and blowing ratio. Higher speed means less benefit from blowing within the limit of blowing ratio of 1. The benefit of using the blowing could come with an increase in the drag at some angle of attack. It is noticed that the blowing technique can generate positive pitching moment at lower angle of attack and can reduce the negative moment when the separation is happening at higher angle of attack. Also, the lesson learned in this paper is that the blowing benefit is more pronounced when the flight is under low Reynolds number environment.